Doping, Law, and Ethics: Safeguarding Fair Competition in Sports - Khayra Suryanto; maulida izza arifin; Qulbi Ratu S E Elamduri (Faculty of Law Universitas Negeri Surabaya, 2025)
Doping In sports Is a pressing and controversial Issue that threatens competitive integrity and athlete health. The use of prohibited substances or methods to enhace performance undermines the principles of sportmanship and fair play. Despite frameworks like the World Anti-Doping Code (WADC) and the efforts of agencies such as WADA, doping athletes to perform at their best. This research explores the legal dimensions of doping within sports law, focusing on the interaction between existing legal frameworks, enforcement challenges, amd athlete rights. Through a comprehensive literature review, this study Identifies health risks associated with doping, evaluates the effectivenes of current anti-doping policies, and examines the motivations behind doping behavior. Notable doping cases are anlyzed to provide insights into the broarder findings higlights the need for a balanced approach that enforces regulation while protecting athletes rights. This research emphasizes the importance of collaboration among legal bodies , sport organizations, and educational entities to foster a fairer and healthier sporting environment. By integrating legal analysis with ethical considerations, the study aims to reinforce accountability and enhance awareness among athletes, ultimately preserving the integrity of sports and promoting athlete welfare. This research contributes to the ongoing discourse on doping by addressing the intersection of law and ethics, advocating for comprehensive strategies that ensure fair competition and safeguard the health of all participants In the sporting community.